Verzerrte Studienergebnisse als Grundlage für politische Entscheidungen? Eine Analyse am Beispiel des Nutztierwohls; Biased Survey Results as Basis of Political Decision-Making - An Analysis using the Example of Farm Animal Welfare - Anne Piper; Rainer Kuḧl (German Journal of Agricultural Economics (GJAE), 2020)
– Survey results may be biased systematically due to a variety of effects. Concomitantly they are often of high relevance for political decision making. This is no problem, as long as effective bias-prevention-methods are applied during the conduction and interpretation of surveys. Regarding social desirability this is usually not the case. Political decisions, based on biased survey results, lead to misallocation. Taking the example of farm animal welfare and using different social desirability scales, the present paper shows, that the citizen-consumer-gap stems from socially desirable response behavior in previous consumer surveys. Therefore, their results should not be taken implicitly as a basis for political or business investment decisions. In addition, further causes of the citizen-consumer-gap concerning farm animal welfare are analyzed.
Keywords: 330